The Middle Ear Microbiota in Healthy Dogs Is Similar to That of the External Ear Canal - Caroline Leonard; Pierre P. Picavet; Jacques Fontaine; Cécile Clercx; Bernard Taminiau; Georges Daube; Stéphanie Claeys (Veterinary Sciences, 2023)
Otitis media can be a consequence of chronic otitis externa and could represent a perpetuating factor. While the microbiota of the EEC in healthy dogs and in the presence of otitis externa has been described, only sparse information is available concerning the normal microbiota of the middle ear. The objective was to compare the tympanic bulla (TB) with the external ear canal (EEC) microbiota in healthy dogs. Six healthy experimental Beagle dogs were selected based on the absence of otitis externa, negative cytology and bacterial culture from the TB. Samples from the EEC and TB were collected directly after death using a total ear canal ablation and lateral bulla osteotomy. The hypervariable segment V1–V3 of the 16S rDNA was amplified and sequenced with a MiSeq Illumina. The sequences were analyzed by the Mothur software using the SILVA database. No significant differences between the EEC and TB microbiota for the Chao1 richness index (p = 0.6544), the Simpson evenness index (p = 0.4328) and the reciprocal Simpson alpha diversity (p = 0.4313) were noted (Kruskal-Wallis test). A significant difference (p = 0.009) for the Chao1 richness index between the right and left EEC was observed. The microbiota profile was similar in the EEC and the TB of the Beagles.